2011
DOI: 10.1037/a0024656
|View full text |Cite
|
Sign up to set email alerts
|

Trainees with professional competency problems: Preparing trainers for difficult but necessary conversations.

Abstract: Trainees with professional competency problems, also called problems of professional competence SUE C. JACOBS, Associate Professor, Training Director, and Ledbetter Lemon Endowed Diversity Professor in Counseling Psychology at Oklahoma State University earned her PhD from the University of Southern Mississippi in 1989. Her interests include issues in ethics, education and training, difficult dialogues, the teaching of psychology, older adults, health, diversity, social justice, disaster response, mindfulness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 45 publications
1
54
0
1
Order By: Relevance
“…When trainers are silent, immobilized, or avoidant regarding competence problems in themselves, colleagues, or trainees, trainees fail to benefit from the modeling so essential for transmitting communitarian competen cies (Elman, Illfelder-Kaye, & Robiner, 2005;Jacobs et al, 2011). Johnson andcolleagues (2012, 2013b) recently encouraged training-focused organizations within professional psychology to take up the challenge of "training the trainers" in communitarian ideals and collaborative training strategies so that they can model communitarian concepts in transparent actions.…”
Section: Ensure That Trainers Model Communitarian Virtues and Behaviorsmentioning
confidence: 97%
“…When trainers are silent, immobilized, or avoidant regarding competence problems in themselves, colleagues, or trainees, trainees fail to benefit from the modeling so essential for transmitting communitarian competen cies (Elman, Illfelder-Kaye, & Robiner, 2005;Jacobs et al, 2011). Johnson andcolleagues (2012, 2013b) recently encouraged training-focused organizations within professional psychology to take up the challenge of "training the trainers" in communitarian ideals and collaborative training strategies so that they can model communitarian concepts in transparent actions.…”
Section: Ensure That Trainers Model Communitarian Virtues and Behaviorsmentioning
confidence: 97%
“…Supervisors do so in a manner that is clear, direct, and mindful of the barriers to assuring that such conversa tions are effective and likely to maintain the supervisory relationship (Hoffman et al, 2005;Jacobs et al, 2011). Conversations addressing competence problems shall oc cur with sensitivity to issues of individual and cultural differences (Constantine & Sue, 2007;Shen-Miller et al, …”
Section: O M a I N F: P R O F E S S I O N A L C O M P E T E N C E Pmentioning
confidence: 98%
“…Research suggests that this motivation is strong to protect a current identifiable patient; however, the effect is noticeably weaker for protecting future lives through the development of safer procedures via feedback (Schwappach & Gehring, ). Jacobs et al () identified that the culture or policies of a workplace, such as unspoken rules or lack of policies to deal with such situations, can contribute to a person's reluctance to engage in a difficult conversation. This is reflected in many paramedics' opinion that the ability to speak up in the workplace would be strengthened by organizational support.…”
Section: Discussionmentioning
confidence: 99%
“…Additional barriers include time pressures, low confidence of ability or belief that it is “not their job” (Maxfield et al, ), empathy for the person involved (Jacobs et al, ), as well as limited belief that their action will lead to any meaningful change (Maxfield et al, ; Martinez et al, ). Although responses were limited by the questionnaire in our study, the majority of paramedics identified a lack of organizational support and service delivery pressures as factors in not speaking up.…”
Section: Discussionmentioning
confidence: 99%